Development and Validation of the DiAbeTes Education Questionnaire (DATE-Q) to Measure Knowledge Among Diabetes and Prediabetes Patients Attending Cardiac Rehabilitation Programs. Issue 4 (26th July 2021) - Ghisi, Gabriela Lima de Melo; Aultman, Crystal; Konidis, Renee; Foster, Evelyn; Sandison, Nicole; Alavinia, Mohammad; Sarin, Michael; Oh, Paul
Abstract : Supplemental Digital Content is Available in the Text. Knowledge assessment tools are highly useful in clinical practice, as they help healthcare teams to customize education and clinical care plans. Based on patients' information needs and diabetes education standards, experts developed 20 items to comprise the DiAbeTes Education Questionnaire (DATE-Q), which was psychometrically tested in 84 patients with diabetes attending cardiac rehabilitation and demonstrated good validity. Abstract : Purpose: Knowledge assessment tools are highly useful in clinical practice, as they help health care teams to customize education and clinical care plans based on the needs of patients. The objective of this study was to develop and validate the DiAbeTes Education Questionnaire (DATE-Q) to measure knowledge among diabetes and prediabetes patients attending cardiac rehabilitation (CR). Methods: Based on patient information needs, other validated tools and diabetes education standards and current practices, experts developed 20 items to comprise the first version of the DATE-Q. To establish content validity, they were reviewed by an expert panel (n = 12) and patients. Refined items were psychometrically tested in 84 diabetes and prediabetes patients attending CR. The internal consistency was assessed via regularized factor analysis and Cronbach α, and criterion validity with regard to patient education and family income. For interpretability analysis, the minimal clinically important difference (MCID) was estimated using distribution- and anchor-based methods. Results: All items were appropriate for administration in this population according to experts and patients. Three factors were extracted and were generally internally consistent and well defined by the items. Criterion validity was supported by significant differences in mean scores by family income ( P < .05). Results showed that increases in knowledge can moderately increase mean steps/d and peak oxygen uptake, with an MCID of 2.13. Conclusions: This study demonstrated preliminary validity of the DATE-Q. Future research is needed to assess other measurement properties to confirm the applicability of this tool in clinical and research settings.